2011
DOI: 10.1007/s00436-011-2625-8
|View full text |Cite
|
Sign up to set email alerts
|

Tungiasis in a free-ranging jaguar (Panthera onca) population in Brazil

Abstract: Tungiasis is an ectoparasitic disease caused by fleas of the genus Tunga. The disease is reported to occur mostly in human populations. In wildlife, however, the occurrence and impact of this disease remains uncertain. We captured and examined 12 free-ranging jaguars for the presence of Tunga penetrans in the Pantanal region of Mato Grosso do Sul state, Brazil. Tungiasis prevalence was 100% in the population; lesions were confined to the jaguar's paws. T. penetrans was identified based on the characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 13 publications
0
14
0
2
Order By: Relevance
“…Among the 13 known species of Tunga , T. penetrans is the most promiscuous, having been found on hosts belonging to eight different orders of mammals, including Cingulata, Pilosa, Artiodactyla, Perissodactyla, Carnivora, Rodentia, Primates, and Proboscidea; in total, T. penetrans has been found on 27 genera of wild and domestic animals (De Avelar 2010) in addition to two occurrences that have only recently been recorded (Frank et al 2012; Widmer and Azevedo 2012). However, in spite of the broad spectrum and category of hosts, the pig is considered the most important animal reservoir for T. penetrans (Pampiglione et al 1998; Ugbomoiko et al 2008).…”
Section: Hostsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the 13 known species of Tunga , T. penetrans is the most promiscuous, having been found on hosts belonging to eight different orders of mammals, including Cingulata, Pilosa, Artiodactyla, Perissodactyla, Carnivora, Rodentia, Primates, and Proboscidea; in total, T. penetrans has been found on 27 genera of wild and domestic animals (De Avelar 2010) in addition to two occurrences that have only recently been recorded (Frank et al 2012; Widmer and Azevedo 2012). However, in spite of the broad spectrum and category of hosts, the pig is considered the most important animal reservoir for T. penetrans (Pampiglione et al 1998; Ugbomoiko et al 2008).…”
Section: Hostsmentioning
confidence: 99%
“…Regarding T. penetrans , approximately 80 lesions were found on dogs, 50 on cats, 16 on rats, and 199 on humans from Fortaleza, Brazil (Heukelbach et al 2004a), whereas in a community in rural Nigeria, Ugbomoiko et al (2008) observed the following maximum numbers of lesions: 184 on pigs, 21 on dogs, and 13 on Rattus rattus . In a study of flea infestations of Panthera onca , Widmer and Azevedo (2012) recorded more than 20 lesions on a young female.…”
Section: Infestationmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Há necessidade de se implementar programas edu- Animais são conhecidos como importantes reservatórios, e a tungíase, considerada uma zoonose. 1,23 A presença de ratos e animais errantes, ou animais domésticos como gatos e cães, favorece a disseminação da pulga no ambiente. Porém, o conhecimento sobre reservatórios da tungíase foi escasso entre os entrevistados, e mais da metade deles não respondeu a essa questão ou respondeu-a erroneamente.…”
Section: Discussionunclassified
“…Para a elaboração da lista das espécies de sifonápteros assinaladas no estado do Mato Grosso do Sul, as seguintes fontes foram consultadas: Pinto (1930), Guimarães (1942;1953), Lima & Hathaway (1946), Hopkins & Rothschild (1953;1956;1962;1971), Johnson (1957), Nagem (1977), Smit (1987), Linardi & Guimarães (2000), Graciolli et al (2008), Medri (2008) e Widener & Azevedo (2012).…”
Section: Methodsunclassified